Persepsi Wanita Pendulang Emas Terhadap Pendidikan Anak Di Nagari Mundam Sakti Kecamatan IV Nagari Kabupaten Sijunjung - Yunita, Hana Norma; Zusmelia, Zusmelia; Zulfa, Zulfa (Pendidikan Sejarah, 2014)
This thesis discusses the perception of gold prospectors Women Against Childhood Education at the Nagari Mundam Sakti Kecamatan IV Nagari Kabupaten Sijunjung. Formulation of the problem: how the perception of women towards the education of children of gold miners in the Nagari Mundam Sakti Kecamatan IV Nagari Kabupaten Sijunjung and the factors that influence womens perceptions of gold miners on their childrens education. as for research purposes are: to describe womens perceptions of the education of children of gold miners in the Nagari Mundam Sakti Kecamatan IV Nagari Kabupaten Sijunjung and megetahui factors that influence these perceptions. The method used in this paper are: a qualitative descriptive method of analysis. Informant selection techniques done by purposive sampling. Methods of data collection in this study used observation, interview and documentation. The data has been collected and analyzed interactively. Data analysis was performed in this study using the iterative developed by Miles and Huberman. The results of this study show that : 1 ) Perception women gold miners against the education of children in the Nagari Mundam Sakti Kecamatan IV Nagari Kabupaten Sijunjung, the school considers it important is that educated women gold miners who have graduated from high school and college, the school considers it is not important is the 60 % of women are gold miners who only completed primary school and junior high. They assume school just for the rich and who have needs that much to go to school. And the high school will add to unemployment and will cost you a lot. 2 ) factors that influence womens perceptions of the education that gold miners internal factors: physiological ladies gold miners, gold miners interest in women very less for studing children because they see school is still a lot of people who become unemployed, the experience of someone in the past had to send children but it does not work. Then the external factors, namely: the size and placement of less parental relationship with the school, and the intensity and strength of the stimulus that urge someone to motivate children to school.